Al-‘Alāqah al-Mutabādilah Baina al-Īmān wa al-Jihād fī Sabīllilah - Muhammad Hirzin (Al-Jami'ah: Journal of Islamic Studies, 1998)
The word “jihad' has been understood wrongly by some orientalists as a holly war.   Amongst non-muslim societies this meaning is very influential that leads to a misperception that “jihad" is identical with a group of muslims who are, with their weapons, ready to demolish those who do not support Islam.  lronically, this misperception is also common to some   groups of muslims and has   caused   to   religious   fanatism and swept away the teaching of tollerance to other religions. As for "jihad” is one of Islamic teaching, so to perform this teaching needs the true   understanding of it.   Before performing any Islamic teaching, someone mush have "iman" or faith, this is due to the fact that Islam which means obedience is a result of "iman".  Generally, “iman" means believe in God   and   accept   all His   teachings. "Iman” is a power within a man because it can not be compelled to someone.  It is accepted after understanding its rational evidences.  For muslims, it can be a bridge that relates them to their God, and with it they can liberate themselves from material desires. Linguistically, the word “jihad" has some meaning of all efforts to reach something.  In Islamic context this word is often followed by the word “fi sabilillah"   which    means   in   the path of Allah. This means that "jihad” must be done in seeking God's favor. Consequently, a war can be called “jihad fi sabilillah"   if it is done in the purpose of keeping Islamic faith and its honor.  In the Qur’an, this word has no meaning except goodness for all and public   welfare.   In other word, “jihad fi sabilillah" has a broad meaning as all kinds of efforts carried out for the purpose of public benefit. This paper tries to   correct   some   misperception of the   word jihad” that is   identical with holly war.  The paper also relates   "jihad'   to “iman" as it is a starting point of every deed.